2011
DOI: 10.1590/s0103-21002011000100004
|View full text |Cite
|
Sign up to set email alerts
|

Características sociodemográficas, capacidade funcional e morbidades entre idosos com e sem declínio cognitivo

Abstract: OBJETIVO: Descrever as características sociodemográficas, funcionais e clínicas dos idosos com e sem declínio cognitivo residentes na zona urbana de Uberaba-MG. MÉTODOS: Estudo tipo inquérito domiciliar realizado com 2.898 idosos. Foram constituídos dois grupos: grupo 1, idosos com pontuação menor que 13 no Miniexame do Estado Mental e grupo 2 com 13 pontos ou mais nesse exame. Os dados coletados, por meio de instrumento semiestruturado, foram submetidos à análise descritiva e ao teste Qui-quadrado (p<0,05)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
16
0
21

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 19 publications
(20 reference statements)
2
16
0
21
Order By: Relevance
“…33 Similarly, a household survey performed in Uberaba-MG, with 2898 elderly individuals, reported that the group with cognitive decline exhibited the greatest proportion of functional disabilities. 11 It is important to highlight that the sample studied was composed of hypertensive elderly individuals who were mostly sedentary, and therefore predisposed to a greater limitation of functional capacity, due to the severity of their cardiovascular condition, the effects of therapy and associated complications in the brain, heart and kidneys. A lifestyle change, involving the adoption of habits such as physical activity, is essential for the control and prevention of hypertension and cognitive decline, thereby increasing the individual´s quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…33 Similarly, a household survey performed in Uberaba-MG, with 2898 elderly individuals, reported that the group with cognitive decline exhibited the greatest proportion of functional disabilities. 11 It is important to highlight that the sample studied was composed of hypertensive elderly individuals who were mostly sedentary, and therefore predisposed to a greater limitation of functional capacity, due to the severity of their cardiovascular condition, the effects of therapy and associated complications in the brain, heart and kidneys. A lifestyle change, involving the adoption of habits such as physical activity, is essential for the control and prevention of hypertension and cognitive decline, thereby increasing the individual´s quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…Education levels have been reported as one of the most significant determinants of cognitive decline in several studies of the factors associated with this phenomenon. [6][7][8]10,11 Other factors have also been highlighted, such as gender, marital status, smoking and alcohol consumption. 12 Therefore, cognitive dysfunction is determined by a complex association of factors, including individual and social conditions, and can directly affect the quality of life of the elderly individual.…”
Section: Introductionmentioning
confidence: 99%
“…A research that sought to describe sociodemographic, functional and clinical characteristics in elderly individuals with and without cognitive decline, living in an urban area of a city in Minas Gerais, identified an expressive percentage of hypertensive individuals with poor circulation (varicose veins), especially in those who presented with an absence of cognitive decline (17) . Another study regarding cognitive loss and health conditions in elderly individuals demonstrated that 5.2% of them, aged between 60 and 75 years, affirmed not having any diseases; 25.9% had one; 25.9% had two; 23% had three; 9.6% had four diseases; 59% had five; and finally 4.4% had six or more diseases (18) .…”
Section: Discussionmentioning
confidence: 99%
“…Individual demographic and socioeconomic characteristics, such as older age, female gender and low level of education 8,9,10 have a well-established association with cognitive decline. However, the influence of environmental socioeconomic factors on cognitive loss among the elderly population has not been so thoroughly investigated.…”
Section: Introductionmentioning
confidence: 99%